Gastrointestinal bleeding prophylaxis in internal medicine patients of a univeristy hospital - Diaztagle-Fernández, Juan José; Sprockel-Díaz, John Jaime; Mojica-Corzo, Ezequiel Masdeeiner; Vásquez-Hoyos, Leonidas; Cruz-Buitrago, Roberto Hernando; Eslava-Orozco, David Felipe; Hernández-Aguirre, Andrés Camilo; Navarro-Noguera, Juan Carlos; Chaves-Santiago, Walter Gabriel (Universidad y Salud, 2022)
Introduction: Anti-ulcer medications are frequently used in hospitalized patients, yet their use is not usually indicated. Objective: To describe the frequency of prescription and indication of medications to prevent gastrointestinal bleeding in hospitalized patients. Materials and methods: A cross-sectional, descriptive, prospective study was carried out in the Internal Medicine service of the Surgery Society of Bogota-San Jose Hospital of Bogota (Colombia). Excluded patients were those with either a gastrointestinal bleeding diagnosis or a history of allergy to anti-ulcer medications. Demographic data and information regarding prescribed medications were collected. It was determined whether the medicine indication was adequate and the type of prescription error was identified. Results: 179 patients were included in the study, 57% (102) of which were women. The average age was 61.3 (±20.2) years old. Infectious disease was the main admission diagnosis (76; 42.4%). A 92.17% (165) of the total number of patients received medications to prevent gastrointestinal bleeding. This indication was adequate for 75 (41.89%) patients. The most frequent error was their use in bleeding low-risk patients (101; 97.1%). Conclusion: A high percentage of patients received medication to prevent gastrointestinal bleeding. However, in about half of these patients it was not indicated.